2021
DOI: 10.1002/brb3.2430
|View full text |Cite
|
Sign up to set email alerts
|

Genetic effects on educational attainment in Hungary

Abstract: Introduction:Educational attainment is a substantially heritable trait, and it has recently been linked to specific genetic variants by genome-wide association studies (GWASs). However, the effects of such genetic variants are expected to vary across environments, including countries and historical eras. Methods:We used polygenic scores (PGSs) to assess molecular genetic effects on educational attainment in Hungary, a country in the Central Eastern European region where behavioral genetic studies are in genera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…We found that after German reunification the magnitude of the association between education-genetics and educational attainment increased in East Germans, who experienced a monumental shift from a state-socialist to a free-market West German system. This aligns with previous reports that the association between education-genetics and educational attainment increased in Estonia and Hungary after the fall of the Soviet Union in Europe (Rimfeld et al, 2018; Ujma et al, 2022). Notably, our time-concurrent regional contrast between East and West Germany substantially reduces the likelihood of cohort-related confounds that could affect genetic associations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that after German reunification the magnitude of the association between education-genetics and educational attainment increased in East Germans, who experienced a monumental shift from a state-socialist to a free-market West German system. This aligns with previous reports that the association between education-genetics and educational attainment increased in Estonia and Hungary after the fall of the Soviet Union in Europe (Rimfeld et al, 2018; Ujma et al, 2022). Notably, our time-concurrent regional contrast between East and West Germany substantially reduces the likelihood of cohort-related confounds that could affect genetic associations.…”
Section: Discussionsupporting
confidence: 92%
“…With the fall of European state-socialism in 1989/1990, East Germany’s educational ideology of non-meritocratic access restriction was rapidly replaced by West German meritocratic ideology geared towards free-market productivity (Littler, 2017; Rohde, 2023; Solga, 2005). Previous studies have found that the association between education-genetics and educational attainment in Estonia and Hungary increased after the fall of the Soviet Union in Europe (Rimfeld et al, 2018; Ujma et al, 2022). Here we examine geographical and historical differences in polygenic associations with educational attainment in East and sWest Germany before and after reunification .…”
Section: Main Textmentioning
confidence: 99%